The Spirituality, Meaning in Life and Depressive Symptomatology in Drug Addiction - Kleftaras, Georgios (The international journal of religion and spirituality in society, 2015)
Spirituality is a topic of increasing interest to clinicians and researchers interested in addiction. A fundamental dimension of spiritual wellness is meaning in life. A review of a large number of studies demonstrates that people who report greater meaning in their lives also report greater well-being, lesser psychopathology, greater spirituality, and greater overall well-being. The purpose of this study was to examine the relationship between meaning in life, spirituality and their dimensions and depressive symptomatogy in drug addiction users. A sample of 300 drug addicts’ patients completed four questionnaires on spirituality, meaning of life, depressive symptomatology and socio-demographic characteristics. Results indicated that the association between spirituality, meaning in life, drug addiction and depressive symptoms was statistically significant. In particular, depression had strong positive correlation with all the subscales of the spirituality questionnaire (ASPIRES) as well as with all of the scales of the meaning in life questionnaire (LAP-R) except for the existential vacuum, where a small negative correlation was found. The findings highlight the importance of spirituality and meaning in life in drug therapy, especially in the treatment of depressive symptoms, which are so frequently associated to drug addiction, and therefore point to the development of therapeutic programmes that take those in to consideration.